ANALISIS PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KOMITE TERHADAP PENGUNGKAPAN RISIKO (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 dan 2019) - Jones Ramos; Nur Cahyonowati (Diponegoro Journal of Accounting, 2022)
This research aims to examine the association of the board of commissioner and committee characteristics on risk disclosure. Characteristics of the board of commissioners used in the research are independent commissioners and expertise of the board of commissioners. The characteristics of committees used are audit committee, expertise of the audit committee, and risk management committee. Control variables used include firm size, leverage, and return on equity.The sample of this research contains the manufacture Indonesian firms listed on Indonesia Stock Exchange. This research used 240 annual reports of the sampled firms over two years from 2018 to 2019. The content analysis approach was used to collect data and to determine the level of risk disclosure in the annual reporting. Multiple regression analysis is used to examine the impact of the characteristics of board of commissioners and committees on risk disclosure.The results show that the presence risk management committee has a significant effect on the extent of risk disclosure. The other board and committee characteristics do not have significant influence on risk disclosure. These results indicate that the role of the board of commissioners and committees has not fully explained the ruling mechanism related to the company's risk control and supervision activities.